Pulse Corticosteroid Therapy for the Complete Reversal of Severe Bilateral Sudden Sensorineural Hearing Loss in High-Activity Systemic Lupus Erythematosus: A Comprehensive Case Report - Ida Ayu Ide Larassanthi Pratiwi; I Made Wiranadha; I Gede Wahyu Adi Raditya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Sudden sensorineural hearing loss (SSNHL) is an alarming otologic emergency. While predominantly idiopathic, it can manifest as a rare, severe complication of autoimmune disorders, including systemic lupus erythematosus (SLE). The underlying pathophysiology in SLE-induced SSNHL often involves aggressive microvascular compromise and immune complex deposition. Case presentation: We present the case of a 21-year-old female with a history of SLE, congestive heart failure, and previous non-hemorrhagic stroke, who presented with acute-onset bilateral hearing loss of one day's duration. She exhibited high SLE disease activity with a MEX-SLEDAI score of 12. Initial pure-tone audiometry revealed very severe SSNHL in the right ear (Air Conduction [AC] 98.75 dB) and severe SSNHL in the left ear (AC 87.5 dB). Due to resource constraints, advanced immunological testing was unavailable; however, a severe lupus flare was confirmed clinically. The patient was immediately treated with intravenous methylprednisolone pulse therapy (500 mg/day) followed by an oral tapering regimen. Subsequent audiometric evaluations demonstrated rapid, complete audiological recovery to normal thresholds bilaterally. Conclusion: High-dose systemic corticosteroid pulse therapy, when initiated within 24 hours of symptom onset, can achieve complete reversal of severe bilateral SSNHL in patients with high-activity SLE. Rapid recognition and aggressive immunosuppression are vital to rescuing cochlear function, even in resource-limited clinical environments.